Constructing π‐Electron‐Conjugated Diarylbutadiyne‐Based Polydiacetylene under Molecular Framework Controlled by Hydrogen Bond and Side‐Chain Substituent Position. Issue 8 (29th February 2016) - Tanphibal, Pimsai; Tashiro, Kohji; Chirachanchai, Suwabun
Abstract : Diarylbutadiyne derivatives are ideal monomers for providing the π‐electron‐conjugated system of polydiacetylenes (PDAs). The geometrical parameters for diacetylene topochemical polymerization are known. However, control of the molecules under these parameters is yet to be addressed. This work shows that by simply tailoring diarylbutadiyne with amide side‐chain substituents, the arrangement of the substituents and the resulting hydrogen bond framework allows formation of π‐electron‐conjugated PDA. Abstract : π‐electron‐conjugated polydiacetylene is constructed by controlling the diacetylene monomers under a hydrogen bond network, with a substituent position arrangement which favors topochemical polymerization. This is achieved through the comprehensive study of diarylbutadiynes containing an amide side‐chain substituent.